Decalibrating the Language. J. H. Prynne’s Biting the Air - Wit Pietrzak, (Miscelánea: A Journal of English and American Studies, 2015)
The article focuses on J.H. Prynne’s 2003 volume Biting the Air. I seek to explore the modes of reconstitution of language that Prynne shows to be enslaved in the various discourses of modernity. The idea of enslaving discourse is shown to be an unacknowledged aspect of modernity on the basis of Don DeLillo’s Cosmopolis and Zbigniew Herbert’s “Report from the Besieged City”, both of which may be seen as illustrations of the hegemony of linguistic enslavement that Prynne struggles against in his poetry. Despite the difference of socio-linguistic and temporal context, both DeLillo and Herbert show that language, as Prynne implies in the ending of Biting the Air, is a “calibrated” mechanism of oppression that, unbeknownst to most people, keeps man fixed within the field of binary rhetoric. In response to that situation, Prynne’s poem is demonstrated to refashion the idiom by emphasizing the multiple process of meaning creation. It is in such decalibration of language that a path may be located beyond the reified linguistic praxis.